Розкопки в Ольвії у 2009 р. на ділянках Б-III та Т-3 - Крижицький, С.Д.; Назарчук, В.І. (Археологічні дослідження в Україні, 2010)
During excavations in 2009 at the new area Б-III in the north-western part of Olbia the remains of a Hellenistic dwelling structure situated near the city defensive wall have been discovered; its planning is partly revealed and one of basement rooms have been studied. Also the research of a dwelling house with the order at the area T-3 has been recommenced. Preliminary revealed planning of a series of rooms to the east from the inner yard of a house needs to be specified; excerptions from its laying were made in the 2nd and the 4th centuries.